IMPLEMENTASI PERDA NOMOR 16 TAHUN 2007 TENTANG KETERTIBAN UMUM (STUDI KASUS PENERTIBAN RUMAH LIAR DI KOTA BATAM) - ", Nuryana; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation Local Regulation No. 16 of 2007 On Public Order (The Case Study is Control of Illegal Houses in Batam) This research aims to identifity and analize the implementation of the local Regulation on Public Order No. 16 of 2007 in Batam, (The Case Study is Control of Illegal Houses in Batam). And then this research can know analized the factors that hindrance the implementation of the Local Regulation on Public Order No. 16 of 2007 in Batam (The Case Study is Control of Illegal Houses in Batam). This research is a qualitative research and the technique of snowball sampling. The results showed that the implementation of the Local Regulation on Public Order No. 16 of 2007 in Batam, it was conducted by the Civil Service Police Unit. But never an absolute order, the Batam residents still live or re-live the illegal of houses region. There are stil many problems thet arise in that implementation. the factors that hindrance the implementation of enforcement among, namely: basic sizes and policy objectives, policy resources, communication between organizations and implementing activities, characteristics of implementing agencies, economic, social and political conditions, as well as the tendency executor.Keyword: Peraturan Daerah (Local Regulation), Ketertiban Umum (Public Order), Implementasi (Implementation), Rumah Liar (The Illegal house)